Agronomic optimal plant density for semiupright cowpea as a second crop in southeastern Brazil - Soratto, Rogério P. [UNESP]; Matoso, Aline O. [UNESP]; Gilabel, Amanda P. [UNESP]; Fernandes, Fabiana M. [UNESP]; Schwalbert, Rai A.; Ciampitti, Ignacio A. (Wiley, 2020)
Cowpea [Vigna unguiculata (L.) Walp.] cultivars with high yield potential and suitable plant architecture for mechanized harvesting have recently shown a growing interest to be cultivated as a second crop in fall–winter season of southeastern Brazil. The agronomic optimal plant density (AOPD) is one of the main management factors defining attainable yield. However, in the scientific literature for semiupright cowpea cultivars grown in fall–winter season in southeastern Brazil the AOPD is not yet clearly defined. A 3-yr study was conducted to evaluate the effect of five plant densities (100,000–500,000 plants ha−1) on growth, seed yield and its components for two cowpea cultivars (BRS Guariba and BRS Novaera) in Botucatu, southeastern Brazil. The AOPD for cowpea increased as the attainable yield improved. The increase in plant density promoted increases in leaf area index (LAI) and the position (measured in height) of the first pod insertion for cowpea plants, but negatively affected per-plant scale surviving rate, leaf area, aboveground dry matter (DM), and yield resulting from intraspecific competition. Maximum cowpea seed yields were achieved with AOPD ranging from 216,630 to 290,537 plants ha−1 (8–24% greater than under the lowest plant density). On average, 259,000 plants ha−1 was estimated for the AOPD to achieve maximum seed yield of semiupright cowpea grown as a second crop in fall–winter season in southeastern Brazil.